2013
DOI: 10.1111/jne.12033
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐relation between Interleukin (IL)‐1, IL‐6 and Body Fat Regulating Circuits of the Hypothalamic Arcuate Nucleus

Abstract: Interleukin (IL)-1 and IL-6 are immune modulating cytokines that also affect metabolic function because both IL-1 receptor I deficient (IL-1RI⁻/⁻) and IL-6 deficient (IL-6⁻/⁻) mice develop late-onset obesity and leptin resistance. Both IL-1 and IL-6 appear to target the central nervous system (CNS) to increase energy expenditure. The hypothalamic arcuate nucleus (ARC) is a major relay between the periphery and CNS in body fat regulation (e.g. by being a target of leptin). The present study aimed to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 56 publications
(134 reference statements)
4
30
2
1
Order By: Relevance
“…The decreased levels of Ucp2 in the hypothalamus of IL6Rα NesCre mice may have been a method for increasing the body temperature of these mice. In a previous study by our group an increase in the mRNAs of the orexigenic genes Agrp and Npy was noted in the hypothalamus of IL6-/mice compared with Wt mice after 4 weeks at cold ambient temperature (32). This was not as evident after 6 days of cold exposure, but was close to reaching significance for Npy in this present study.…”
Section: Discussionsupporting
confidence: 82%
“…The decreased levels of Ucp2 in the hypothalamus of IL6Rα NesCre mice may have been a method for increasing the body temperature of these mice. In a previous study by our group an increase in the mRNAs of the orexigenic genes Agrp and Npy was noted in the hypothalamus of IL6-/mice compared with Wt mice after 4 weeks at cold ambient temperature (32). This was not as evident after 6 days of cold exposure, but was close to reaching significance for Npy in this present study.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, which was conceived without strong proinflammatory stimulus, we showed that exenatide increased the expression of IL-1β, which, in paracrine way, may be responsible for altered feeding behaviors. Previously, it was shown that IL-1β had anorexigenic properties and could affect body weight at the hypothalamic level (35). Of note, we noted that exenatide had the ability to elevate the level of IL-1β under normoglycemic culture conditions, which is concordant with the extended therapeutic indications of GLP-1 agonists to treat obesity even without coexisting diabetes.…”
Section: Discussionsupporting
confidence: 80%
“…In support of this hypothesis, mice lacking IL-6 developed late-onset obesity; injections of IL-6 to IL-6 −/− mice partially reversed this obesity (Wallenius et al, 2002). Although the mechanisms are not understood, neurons of the hypothalamic arcuate nucleus, primarily in the ventromedial region of the nucleus, express the obesity promoting Neuropeptide Y (NPY), which increases food intake (Schele et al, 2013;Senaris et al, 2011). The authors concluded that IL-6 might act directly on neurons of the hypothalamic arcuate nucleus, inhibiting the expression of NPY and thus reducing food intake.…”
Section: Il-6 and Obesitymentioning
confidence: 88%